Analisis Aqad Muzara’ah dan Musaqah - Ahmad Syaickhu; Nik Haryanti; Alfin Yuli Dianto (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2020)
This journal aims to explain how aqad Muzara’ah and Musaqah, Cooperation in agricultural land has actually existed since long ago until now. However, what is happening now is that the cooperation between them (land owners and tenants) is usually called paroan sawah, where the contract is not written down but only verbally. This often results in losses on the one hand, because there is no evidence. In Islamic banking, the most widely used principles are deliberation and mudaraba, while Muzara’ah and are used specifically for plantation or agricultural financing by several Islamic banks. Muzara’ah has it has from the only the passing, the Italy'ah limited on the plant that were like, rice, ginger, the potato. As for annual crops, the musaqat scheme can be used. Because of the specific nature of this Muzara’ah, most Islamic banks use deliberation or greetings for agricultural business credit. However, in its development, the practice of Muzara’ah tends to be mudaraba (cooperation with a profit sharing system). Technically mudaraba is a business cooperation contract between two parties in which the first party (shahib al maal) provides all the capital, while the other party is called mudharib as the business manager. Profits in mudaraba will be shared by the agreement set forth in the contract. Meanwhile, the loss will be borne by the party making the negligence.